METHODOLOGY FOR MANAGING A COMPLEX OF INFORMATION SERVICES IN E-COMMERCE (International journal of artificial intelligence, 2026)
This study examines methodological approaches to managing a complex of information services in e-commerce under conditions of digitalization and growing platform-based competition. Information services are viewed as an integrated system that supports data processing, customer interaction, transaction execution, and managerial decision-making. The research synthesizes contemporary theories of information systems, service-dominant logic, data governance, and platform management to justify a holistic management framework. Special attention is given to the interdependence between data quality, service reliability, trust, and business performance. The study highlights the role of governance mechanisms, analytical tools, and organizational coordination in ensuring the effective functioning of information services. It is argued that fragmented management of digital services limits adaptability and reduces value creation in e-commerce environments. The proposed methodological approach emphasizes system integration, continuous monitoring, and alignment between strategic objectives and operational processes. The findings contribute to the theoretical understanding of e-commerce management and provide a conceptual basis for improving the efficiency and sustainability of information service systems in digital markets.